Clinical and Objective Cognitive Measures for the Diagnosis of Cognitive Frailty Subtypes: A Comparative Study - Ruan, Qingwei; Zhang, Weibin; Ruan, Jian; Chen, Jie; Yu, Zhuowei (Frontiers in Psychology, 2021)
BACKGROUND: Cognitive frailty (CF) includes reversible and potential reversible two subtypes. The former is referred as concurrent physical frailty and pre-mild cognitive impairment (MCI), and the latter is defined as concurrent physical frailty and MCI. The diagnosis of pre-MCI SCD and MCI was based on clinical criteria, including clinical MCI criteria and various subjective cognitive decline questionnaires. Heterogeneous assessment of cognitive impairment is an important cause that results in significant variability of cognitive impairment, CF and their subtype prevalence in various population-based studies. OBJECTIVE: We established objective criteria of cognitive frailty (CF) subtypes based on the norm-adjusted 6 neuropsychological test scores and investigated whether clinical CF criteria based on clinical mild cognitive impairment (MCI) criteria combined with the subjective cognitive decline questionnaire (SCD-Q) can efficiently discriminate between individuals with different CF subtypes. METHODS：Of the 5,328 community-dwelling older adults, 335 volunteers (aged 60 years or older) were recruited, including 94 MCI, 97 pre-MCI SCD determined by clinical diagnosis, and 144 robust normal based on objective cognitive assessment, in the study (September 2018– June 2019). Volunteers with MCI or pre-MCI SCD determined by clinical cognitive assessment were reclassified into different Z-scores derived subgroups based on objective cognitive or CF criteria, and the diagnostic accuracy were compared between neuropsychological test raw scores and clinical measure scores among these subgroups. Cognitive status was further compared in different subgroups after adjusting for age, gender, and education level. RESULTS: After reclassification, the objective assessments indicated better performance than clinical assessments to discriminate cognitive impairment severity among different subgroups. After adjusting covariates, clinical assessments significantly improved the ability to discriminate cognitively normal individuals from those with pre-MCI SCD and MCI but not between z-scores derived from the robust normal group. Furthermore, the adjustment did not improve the ability to discriminate individuals with reversible CF from those with potentially reversible CF and only pre-MCI SCD from only MCI. CONCLUSIONS: Objective criteria are better than clinical criteria for the diagnosis of cognitive impairment in individuals with CF subtypes. Rapid conventional cognitive screening in combination with normative z-scores criteria is cost-effective and sustainable in clinical practice.